FORMULASI KEBIJAKAN PENETAPAN UPAH MINIMUM PROVINSI (UMP) DI SULAWESI TENGAH - Mahripin, Mahripin (Katalogis, 2015)
Minimum wage is the lowest monthly wage consists of basic salary and fixed allowance for labour employee by the governor as a safety net. In determining the provincial minimum wage by the governer, it is initially through thr formulating process by provincial wage boar. Provincial wage council member consists of executives, enterpreneurs, and employees/labor. (Tripartite). In the formulation process of the provincial minimum wage by the provincial wage council, it should be based on valid data of living needs. Valid data of living needs is obtained through surveys team which is established by the provincial wage council. The purpose of the research is to identify and explain the process of formulation of provincial minimum wage determination in Central Sulawesi. The research is a qualitative descriptive research. Data collection is conducted trough observation, interviews and documentaion. The theory used is the theory of William N. dunn, which emphasizes on five aspects namely: 1). Problem formulation, 2). Forecasting, 3). Recommendation, 4). Monitoring and 5). Evaluation. The result shows that the policy formulation of provincial minimum wage in Sentral Sulawesi has not been through the rigth stages of formulation process, because there are aspects that are not met, namely the aspect of problrm formulation. Non fullfillment of problem formulation aspect is caused by invalid data of living needs which is used as a condition of provincial minimum wage determination by the governer of Central Sulawesi. Provincial wage council of Central Sulawesi conpires in engineering thr survey data of living needs which weaken the labors/employees in the posisition of formulation process of Provincial minimum wage.. Survey data is only as a formality of normative administration fullfillment, the provincial wage council of Central Sulawesi uses the regulation of minister of labor and transmigration No. 13 of 2012 on components and implementation of living needs achievement only as a formality. Forecasting, recommendation, monitoring and evaluation stages has been implemented although it is not perfect as stated in the applicable regulation (regulation of the minister of labor and transmigration number 7 of 2013 concerning minimum wage).